2015
DOI: 10.1038/srep16713
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Ih expressed in IB4-negative Aδ nociceptive DRG neurons contributes to mechanical hypersensitivity associated with cervical radiculopathic pain

Abstract: Cervical radiculopathy represents aberrant mechanical hypersensitivity. Primary sensory neuron’s ability to sense mechanical force forms mechanotransduction. However, whether this property undergoes activity-dependent plastic changes and underlies mechanical hypersensitivity associated with cervical radiculopathic pain (CRP) is not clear. Here we show a new CRP model producing stable mechanical compression of dorsal root ganglion (DRG), which induces dramatic behavioral mechanical hypersensitivity. Amongst noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…This is inconsistent with our previous report in IB4 − Aδ neurons where CRP condition produces obvious shift of V 0.5 of I h in depolarizing direction. 4 This discrepancy might be due to different changes in kinetics of HCN channels responsible for I h in different subgroups of DRG neurons under CRP states. Taken together, chronic compression of cervical DRGs produced obvious upregulation of I h in large DRG neurons, this extends our previous report in nociceptive IB4 − Aδ DRG neurons under CRP condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is inconsistent with our previous report in IB4 − Aδ neurons where CRP condition produces obvious shift of V 0.5 of I h in depolarizing direction. 4 This discrepancy might be due to different changes in kinetics of HCN channels responsible for I h in different subgroups of DRG neurons under CRP states. Taken together, chronic compression of cervical DRGs produced obvious upregulation of I h in large DRG neurons, this extends our previous report in nociceptive IB4 − Aδ DRG neurons under CRP condition.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, chronic compression of cervical DRGs produced obvious upregulation of I h in large DRG neurons, this extends our previous report in nociceptive IB4 − Aδ DRG neurons under CRP condition. 4 …”
Section: Resultsmentioning
confidence: 99%
“…The treating physician later estimated the frequency regularly during patient follow-ups. The patients demonstrated sensory abnormalities on the clinical examination of the sensory territories of C2 and/or C3 including brush allodynia (15), Von Frey filaments testing (16), pressure algometer (17), and hypoesthesia to touch and pinprick testing (18). Patients also showed tenderness to paraspinal, supraorbital, and/or jaw skin roll technique (19).…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…Several ionic currents have been implicated in the membrane excitability and repetitive firing in neurons including I NaP , I h [ 15 , 38 , 39 , 40 ]. Previous studies in mesencephalic V neurons have reported a crucial role of I Na,P in the determination of excitability type [ 13 ].…”
Section: Discussionmentioning
confidence: 99%